Application of biotechnology in disease diagnosis and vaccine Development - Masake, R.A.; Musoke, A.J.; Ole-MoiYoi, O.K. (Zimbabwe Biotechnology Advisory Committee, 1996)
Advances in biotechnological techniques are driven by the needs of the human populations. The new techniques in biotechnology have been developed as a consequence of the integrated use of microbiology, biochemistry and chemical engineering. Some of these technologies are being employed in the derivaton of novel methods for improvement of animal production, diagnosis and control of diseases having adverse effects on livestock production in Africa. The majority of the cattle in Africa are of the humped Zebu type (Bos indicus) in East Africa and taurine (Bos taurus), humpless, and smaller sized animals (N'Dama and Baoule) in West Africa. these breeds of cattle yield relatively less milk and beef compared to European breeds such as Friesians. Despite the low productivity of the N'Dama, Baoule and Zebu cattle, they exhibit resistance to a number of diseases prevalent on the African continent unlike the European breeds which readily succumb to such diseases. Hence, a significant component of research on animal production is adapted towards Development of breeds with a high milk and beef yield, but that are less susceptible to the pathological effects of diseases prevalent in Africa. Research conducted by ILRI is partly designed to improve control of three disease complexes, namely, trypanosomiasis, tick-borne disease and helminthiasis. These diseases are responsible for severe production and economic losses throughout sub Saharan Africa. This paper addresses the applications of biotechnology to animal breeding, diagnosis and vaccine Development for control of trypanosomiasis and tick-borne diseases.